2020
DOI: 10.1111/jcpp.13324
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Reading disorders revisited – the critical importance of oral language

Abstract: This paper discusses research on reading disorders during the period since their classification within the overarching category of neurodevelopmental disorders (Journal of Child Psychology and Psychiatry, 53, 2012, 593). Following a review of the predictors of learning to read across languages, and the role of language skills as critical foundations for literacy, profiles of reading disorders are discussed and putative causal risk factors at the cognitive, biological, and environmental levels of explanation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 162 publications
(166 reference statements)
8
49
0
7
Order By: Relevance
“…Dicha ventaja fue además observada tanto en la calidad de los textos escritos, específicamente, en el número de elementos discursivos propios de la argumentación y en su longitud. Estos resultados coinciden con la idea ampliamente sostenida de que el desarrollo de la lengua escrita está soportado, al menos parcialmente, por la lengua oral (Griffin et al, 2004;Juel, Griffith, & Gough, 1986;Snowling & Hulme, 2020). En este trabajo, la influencia de una modalidad (oral) sobre otra (escrita) se podría haber visto reforzada por el hecho de que ambas intervenciones trabajaban un mismo género discursivo (argumentación), y a que la intervención oral movilizaba la generación de ideas, así como la calidad y la estructura de los argumentos.…”
Section: Efectos Intermodalidadunclassified
“…Dicha ventaja fue además observada tanto en la calidad de los textos escritos, específicamente, en el número de elementos discursivos propios de la argumentación y en su longitud. Estos resultados coinciden con la idea ampliamente sostenida de que el desarrollo de la lengua escrita está soportado, al menos parcialmente, por la lengua oral (Griffin et al, 2004;Juel, Griffith, & Gough, 1986;Snowling & Hulme, 2020). En este trabajo, la influencia de una modalidad (oral) sobre otra (escrita) se podría haber visto reforzada por el hecho de que ambas intervenciones trabajaban un mismo género discursivo (argumentación), y a que la intervención oral movilizaba la generación de ideas, así como la calidad y la estructura de los argumentos.…”
Section: Efectos Intermodalidadunclassified
“…Although it is clear that phonological awareness alone is not sufficient to account for children’s reading ability ( Pennington, 2006 ; McGrath et al, 2020 ), most studies of alphabetic languages have found that children’s phonological awareness is the primary precursor of reading ( Hulme and Snowling, 2013 ; Snowling and Melby-Lervåg, 2016 ; McGrath et al, 2020 ). Given this principle assumption, the predominant view for many years was that children’s reading ability at age 7years and older could be explained by observing their perception of phonetic segments, such as consonants and vowels in high frequency words at the kindergarten level (i.e., at the age of 4–6years; Lyytinen et al, 2015 ; Snowling and Hulme, 2020 ). Many earlier studies have focused on children’s perception and manipulation of the onset (the initial consonant or consonant cluster of the word) and rimes (the vowel and any consonants after the vowel), which are considered as major segments of oral languages ( Bergen et al, 2012 ; Lin et al, 2018 ; McGrath et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a whole range of other possible cognitive factors have, through case-control studies, been suggested as possible influences on learning to read and thereby dyslexia (e.g. among others, auditory and speech deficits, visual processing deficits and learning deficits) (Snowling & Hulme, 2020). However, these candidates have not gained as much support as phonological problems and RAN.…”
mentioning
confidence: 99%
“…Not everyone with dyslexia shows poor phonological skills and not everyone with poor phonological skills goes on to develop reading problems. An influential view is that dyslexia is a condition that depends upon multiple risk factors operating at the cognitive, biological and environmental levels (Pennington, 2006; Snowling & Hulme, 2020).…”
mentioning
confidence: 99%